DRUG-INDUCED LIVER DAMAGE - Saidova Mukhabbat Mukhidinovna; Umarov Firuz Kholmurodovich (Scientific Impulse, 2023)
Drug-induced liver damage (DILD) is a heterogeneous group of clinical and morphological variants of liver damage against the background of medication administration for medical indications in usual therapeutic doses due to both direct toxic (usually predictable) and toxic-immunologic (idiosyncratic) or allergic types of effects. The spectrum of clinical manifestations of drug-induced liver disease is extremely diverse; these manifestations often have similarities to "classical" forms of liver disease. The basis of diagnosis is a carefully collected anamnesis about the drugs used.